L1 translation as scaffolding in tutor talk: a case study of two Korean tutors - Cho, Sookyung; Kim, Suyeon (Penerbit Universiti Kebangsaan Malaysia, 2017)
With the increasing popularity of the communicative approach in the mid-20th century, the use of the L1 was discouraged and stigmatized in foreign language education. Since the emergence of the sociocultural perspective, however, L1 use has been reconsidered as a key mediating tool for second language learning. Utilizing this sociocultural approach, this study examines how L1 translation is used in tutor-tutee talk during writing center appointments by analyzing the talk of two Korean tutors with their seven tutees. The analysis reveals that L1 translation not only helps the tutees clarify their intended meaning in their texts, but also serves as a successful tool for cognitively scaffolding tutee learning—in the forms of pump, hint, and prompt—by helping both the tutor and tutee negotiate meaning and arrive at a solution together. The results bring new insights regarding the use of L1 translation in tutor and tutee interaction by highlighting the usefulness of L1 translation as scaffolding for language learners, particularly when their language proficiency is not advanced. This study implies that the use of L1, in particular, L1 translation may contribute to L2 learners’ learning of English by facilitating their negotiations of meaning with their teachers as to finally arrive at mutual understanding of each other.